The Influence of Organizational Culture and Employee Engagement on Employee Performance Through Job Satisfaction of Employees at Pt Generasi Teknologi Buana - Christiani Novera Sarumpaet; Erny Tajib (Indonesian Journal of Economic & Management Sciences, 2023)
This study aims to analyze the effect of organizational culture and employee engagement on employee performance through job satisfaction. The data used in this study is primary data that comes directly from the object in this study, namely one of the startup companies in Jakarta, PT Generasi Buana Technology. The sample in this study was selected using the non-probability sampling method so that 195 respondents were sampled from a population of 200. Data analysis used descriptive statistics by finding the average and standard deviation, and using AMOS SEM, for hypothesis testing. Previously the instrument had been tested using validity and reliability tests where the results were valid and reliable. The results of the study show that employee engagement has a positive effect on job satisfaction